The rabies virus phosphoprotein synthesis and subcellular localization are modified by nerve growth factor (2009)
Rabies virus P protein participates as a regulating factor in viral transcription and replication; recent studies found an antitranscriptional and antireplicative effect of nerve growth factor (NGF) and Neurotrophin-3 (NT-3) in infected neuron cultures. We investigated here the specific effect of the neurotrophins on P protein, evaluating its synthesis and subcellular distribution in adult mouse dorsal root ganglia neuron cultures infected and treated with NGF or NT-3. The results showed that NGF, but not NT-3, caused an increase in the quantity of P protein and an accumulation of protein in neuronal bodies, revealing changes in transport to the neuritic processes.